Marketing Strategy in Increasing Sales of Muslim Clothing Products at the Petisah Market in Medan City - Atika Aini Nasution; Aryani Sairun; Sugito (International Journal of Economics (IJEC), 2022)
The level of competition in the business world requires every seller to be able to carry out his marketing activities more effectively and efficiently. This study aims to determine the marketing strategy for Muslim fashion products at the Petisah Market in Medan City in increasing sales, and to find out the obstacles encountered in marketing Muslim fashion products at the Petisah Market in Medan City. This research is a field research ( field research ) which is descriptive qualitative in nature. The results of the study show that the marketing strategy carried out by Muslim clothing traders at the Petisah Market in Medan City is to do good segmentation , targeting and positioning , by carrying out a marketing mix related to product , price , place , promotion , people , process , and physical evidence. The obstacles faced in marketing Muslim fashion products at the Medan City Petisah Market, including the lack of capital, delays in the arrival of goods ordered from suppliers, lack of employees and minimal promotion, namely only relying on social media which also has various limitations.